FeCl3-activated carbon developed from coconut leaves: characterization and application for methylene blue removal - Ramlah Abd Rashid,; Ali H. Jawad,; Mohd Azlan Mohd Ishak,; Nur Nasulhah Kasim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In this study, coconut leaves were used as a starting material for the production of activated carbon by thermal carbonization using FeCl3-activation method. The characterization of coconut leaves-FeCl3 activated carbon (FAC) were evaluated by bulk density, ash content, moisture content, point-of-zero charge (pHpzc) analysis, iodine test, scanning electron microscopy (SEM), Fourier transform infrared (FTIR) and elemental (CHNS-O) analysis. The effect of the adsorbent dosage (0.02-0.25 g), initial pH (3-11), initial dye concentrations (30-350 mg/L) and contact time (1-180 min) on the adsorption of the methylene blue (MB) at 303 K was performed via batch experiments. The Pseudo-Second Order (PSO) describes the kinetic model well whereas the Langmuir isotherm proved that adsorption behavior at equilibrium with maximum adsorption capacity (qmax) of 66.00 mg/g.